2001
DOI: 10.1542/peds.108.3.e47
|View full text |Cite
|
Sign up to set email alerts
|

Family Pain History Predicts Child Health Status in Children With Chronic Rheumatic Disease

Abstract: ABSTRACT. Objectives. To examine the relationships of parental and family pain history on the pain experience of children with chronic rheumatic disease. The aims of the study were as follows: 1) to describe the pain history of parents and families of children with rheumatic disease, 2) to examine relationships between parental and family pain history and the pain report and physician-rated health status of children with chronic rheumatic disease, and 3) to determine whether child coping mediates the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
1
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 31 publications
3
66
1
3
Order By: Relevance
“…Our findings on the association between family history of LBP and adolescent LBP confirm those of a previous survey in the same area of Switzerland [48] and those of other studies [49][50][51]; however, there are also studies that report no familial clustering [52]. Whether the association, when observed, is a question of ''nature or nurture'' remains open to speculation.…”
Section: Other Predictors Of Lbpsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings on the association between family history of LBP and adolescent LBP confirm those of a previous survey in the same area of Switzerland [48] and those of other studies [49][50][51]; however, there are also studies that report no familial clustering [52]. Whether the association, when observed, is a question of ''nature or nurture'' remains open to speculation.…”
Section: Other Predictors Of Lbpsupporting
confidence: 88%
“…There is increasing evidence of a hereditary aspect to low back pain [53,54] although exposure to the nature of the problem (and its need for treatment or not) by virtue of upbringing might also play a role. It has been shown that parents who sought more treatment for their own pain were more likely to have children reporting higher levels of pain [51]. As our question specifically mentioned ''having been treated for LBP'' this might have influenced our findings.…”
Section: Other Predictors Of Lbpmentioning
confidence: 82%
“…Multiple factors may affect the onset and persistence of musculoskeletal pain in JIA, including biological influences such as genetic (16), anatomical (16) and disease-related factors (17), psychosocial factors (eg, coping and cognitive health beliefs) (18)(19)(20) and environmental/social cultural context such as parental history of pain (21,22). However, the precise mechanisms through which these factors influence pain are not fully understood (23).…”
Section: Predictors Of Pain In Jiamentioning
confidence: 99%
“…For example, the nature of family relationships, including family harmony and conflict (24), increased parental psychological distress (39), and parent and family history of pain, predicted pain in children with JIA (22). Parent responses to a child's pain also explain the extent to which pain affects the child's physical, emotional and social well-being.…”
Section: Predictors Of Pain In Jiamentioning
confidence: 99%
“…However, the familial environment has also been proposed as being extremely important in understanding pediatric pain and associated disability (11). Parental solicitousness, family conflict, cohesiveness, parental pain history, and coping have all been associated with children's adaptation to chronic pain (11)(12)(13)(14), but further research into the familial context in JPFS and implications for disability in patients with JPFS is needed. Involvement of family members is a necessary component of managing any chronic condition of childhood, and it is important to identify which aspects of the familial environment are important to consider when planning for intervention in adolescents with JPFS.…”
Section: Introductionmentioning
confidence: 99%